Political Law of The State of Indonesia as the State of Pancasila Law in the Framework of the Establishment National Law on the Establishment of Copyright Law - MARZUKI, M; SINTARA, DANI (The journal of contemporary issues in business and government, 2021)
Pancasila as the source of all legal resources is determined by the politics that develop in every ruling regime. During the New Order (Orba) regime in power, Pancasila became a static dogma because it was initiated by applying Pancasila and the Constitution of the Republic of Indonesia in 1945 (abbreviated as the 1945 NRI Constitution) purely and consequently. In the reform era, the existence of Pancasila as the source of all legal resources still obtained the legal house through TAP MPR Number III /MPR/2000 on The Source of Law and The Order of Legislation. However, in this TAP MPR the position of Pancasila is no longer explicitly asserted as the source of all legal resources in the national legal system. This research is normative law research using legal approach and conceptual approach. This research is descriptive analytical using qualitative data analysis. Factors causing the emergence of pro-cons and rejection of the formulation, formation and validity of the Bill of Copyright Work into Law No. 1 of 2020 on Copyright Work, because in the establishment is not participatory, transparent. The regulation on the normative rights of workers in Law No. 11 of 2020 on Copyright work, has not accommodated the normative rights of labor. In fact, the substation of the Labor Act is perceived as ignoring the normative rights of the workforce. The establishment of the Working Copyright Law has not realized the values of Pancasila as the basis of the nation's living philosophy that becomes the main legal source in every legislator. This is known from the substance of the articles on the employment cluster that many do not conform to the values of industrial relations based on the family economic system, which reflects the principles of social justice.